Evaluasi Kualitas Layanan Website Sistem Informasi Akademik Unimor (SIAMOR) Pada Universitas Negeri Timor Menggunakan Technology Acceptance Model (TAM) - Payong, Yohanes (STIKOM Uyelindo Kupang, 2022)
Academic Information System is implemented to assist the organization of academic activities for lecturers and students. The success of the implementation of an academic information system can be measured by means of evaluation. Evaluation of the application of academic information systems to the level of acceptance of the system. In order to use the academic information system optimally, it is necessary to analyze the factors that influence user acceptance of the system. The use of SIAMOR so far has not been maximized because there are several problems such as server disturbances at SIAMOR which cause SIAMOR to be inaccessible for a certain time, there are features that cannot be used or do not work, students have difficulty using SIAMOR because students are not given a manual regarding procedures for using SIAMOR. This study aims to determine the factors that influence the acceptance of the Unimor Academic Information System (SIAMOR) by students. The model used in this study is the Technology Acceptance Model (TAM) with data analysis using Multiple Linear Regression Analysis. This type of data collection was obtained from a questionnaire with a sample of 100 students. The results of the research show that the Perceived Ease of Use partially has no effect on IT Acceptance, Perceived Usefulness does not affect IT Acceptance, Attitude Toward Using partially affects IT Acceptance and Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using affects IT Acceptance